PENGARUH KOMPETENSI DAN SEMANGAT KERJA TERHADAP KINERJA KARYAWAN PT. PERKEBUNAN PENINJAUAN PLASMA BATURAJA - Anwar, Rani (Program Studi Manajemen Fakultas Ekonomi Universitas Palembang, 2021)
This research entitled The Influence of Competence and Working Spirit on Employees’ Performance at PT. Perkebunan Peninjauan Plasma Baturaja. The analytical tool used in this study is multiple linear regression. The purpose of this study was to determine the influence of competence and working spirit on employees’ performance at PT. Perkebunan Peninjauan Plasma Baturaja either partially or simultaneously. From the research results, it was found that simultaneously there was an influence of competence and working spirit on employees’ performance at PT. Perkebunan Peninjauan Plasma Baturaja. Partially competence has a significant influence on the performance of employees at PT. Perkebunan Peninjauan Plasma Baturaja, while working spirit has no influence on the employees’ performance at PT. Perkebunan Peninjauan Plasma Baturaja. The results analysis of the coefficient of determination (Adjusted R Square) were found to be 0.827, this indicated that 82.7% of the variation in employees’ performance (Y) can be explained by the competency (X1) and working spirit (X2) variables, while the remaining 17.3% is influenced by other variables besides the variables in this study such as motivation and communication (Widodo, 2010: 49)